Production of L-Asparaginase using Soil Isolate of Cladosporium sp. and Evaluation of its Antitumor and Antioxidant Activities - Thiyagarajan, Santhanamari (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The enzyme L-asparaginase is given prime attention in healthcare settings owing to its significant therapeutic applications in oncology. The present study isolated five different species of fungi belonging to the genera Aspergillus (23.8 and 9.5%), Cladosporium (19%), Fusarium (14.3%) and Penicillium (19%) from soil samples. Screening on Czapek Dox’s medium indicated that the isolate Cladosporium sp. ASP4 exhibit higher potential of synthesizing L-asparaginase than other fungi by means of causing a halo zone measuring 22.3 mm dia. Fermentation of standard medium ingredients along with the solid substrate soya bean meal by the potential fungal isolate resulted in the production of 20.53 IU/mL of L-asparaginase. Optimization studies deciphered the carbon source sucrose, supplementary nitrogen ammonium nitrate, pH ≥8.0 and the temperature 50oC as favorable process parameters for the enzyme production. Purified L-asparaginase of the present study demonstrated moderate antineoplastic activity against the A549 lung cancer cells with the IC50 values of ≥50 IU/mL. The enzyme displayed better antioxidant property compared to those of previous studies by way of scavenging the radicals with the SC50 values of ≥250 mg/mL. These findings encourage carrying out further elaborate studies for prospective biotechnological and pharmaceutical applications of the purified enzyme.